City features related to obesity in preschool children: a cross-sectional analysis of 159 cities in six Latin American countriesResearch in context - Jessica Hanae Zafra-Tanaka; Ariela Braverman; Cecilia Anza-Ramirez; Ana Ortigoza; Mariana Lazo; Tamara Doberti; Lorena Rodriguez-Osiac; Gina S. Lovasi; Mónica Mazariegos; Olga Sarmiento; Carolina Pérez Ferrer; J. Jaime Miranda (Elsevier, 2023)
Summary: Background: Childhood obesity is a rising global health problem. The rapid urbanization experienced in Latin America might impact childhood obesity through different pathways involving urban built and social features of cities. We aimed to evaluate the association between built and social environment features of cities and childhood obesity across countries and cities in Latin America. Methods: Cross-sectional analysis of data from 20,040 children aged 1-5 years living in 159 large cities in six Latin American countries. We used individual-level anthropometric data for excess weight (overweight or obesity) from health surveys that could be linked to city-level data. City and sub-city level exposures included the social environment (living conditions, service provision and educational attainment) and the built environment (fragmentation, isolation, presence of mass transit, population density, intersection density and percent greenness). Multi-level logistic models were used to explore associations between city features and excess weight, adjusting for age, sex, and head of household education. Findings: The overall prevalence of excess weight among preschool children was 8% but varied substantially between and within countries, ranging from 4% to 25%. Our analysis showed that 97% of the variability was between individuals within sub-city units and around 3% of the variance in z-scores of weight for height was explained by the city and sub-city levels. At the city-level, a higher distance between urban patches (isolation, per 1 SD increase) was associated with lower odds of excess weight (OR 0.90, 95% CI 0.82-0.99). Higher sub-city education was also associated with lower odds of excess weight, but better sub-city living conditions were associated with higher odds of excess weight. Interpretation: Built and social environment features are related to excess weight in preschool children. Our evidence from a wide range of large Latin American cities suggests that urban health interventions may be suitable alternatives towards attaining the goal of reducing excess weight early in the life course. Funding: The SALURBAL project (Salud Urbana en América Latina, Urban Health in Latin America) is funded by Wellcome [205177/Z/16/Z].